Genetic diversity of Staphylococcus aureus influences disease phenotype of systemic lupus erythematosus. (30th September 2020) - Ceccarelli, Fulvia; Lo Presti, Alessandra; Olivieri, Giulio; Angeletti, Silvia; Perricone, Carlo; Garufi, Cristina; Iaiani, Giancarlo; De Florio, Lucia; Antonelli, Francesca; De Cesaris, Marina; Giordano, Alessandra; Amori, Luigino; et al.
Abstract: Objective: We investigated the genetic diversity, molecular epidemiology and evolutionary dynamics of Staphylococcus aureus (SA) isolated from SLE patients by means of phylogenetic analysis. Methods: Consecutive SLE patients (ACR 1997 criteria) were enrolled: clinical/laboratory data were collected and nasal swab for SA identification was performed. On the basis of the translation elongation factor ( tuf ) gene, a phylogenetic analysis was performed to investigate relationships and to assess significant clades. Selective pressure analysis was used to investigate the evolution of the SA tuf gene. The gene sequences from non-SLE individuals, downloaded from the GenBank database, were compared through phylogenetic analysis with the tuf gene from SLE patients. Results: We enrolled 118 patients [M/F 10/108; median (interquartile range (IQR)) age 45.5 (13.2) years; median (IQR) disease duration 120 (144) months]. Twenty-four patients (20.3%) were SA carriers (SA + ), three of them MRSA. SA + SLE showed significantly higher SLEDAI-2k values [SA + : median (IQR) 2 (3.75); SA − : 0 (2); P = 0.04]. The phylogenetic analysis, restricted to 21 non-MRSA SA +, revealed a statistically supported larger clade (A, n = 17) and a smaller one (B, n = 4). Patients located in clade A showed a significantly higher prevalence of joint involvement (88.2%) in comparison with clade B (50.0%, P < 0.0001) and SA − (62.7%, P < 0.0001). Haematological manifestations were significantly more frequent in clade A (64.7%) compared with B (50.0%, P = 0.004). Conclusion: We suggest a possible role of SA nasal carriage status in SLE disease activity. Moreover, our findings support the hypothesis that bacterial genetic variants may be associated with specific disease features.